Transmission of Foot-and-Mouth Disease Virus during the Incubation Period in Pigs - Stenfeldt, Carolina; Pacheco, Juan M.; Brito, Barbara P.; Moreno-Torres, Karla I.; Branan, Matt A.; Delgado, Amy H.; Rodriguez, Luis L.; Arzt, Jonathan (Frontiers in Veterinary Science, 2016)
Understanding the quantitative characteristics of a pathogen’s capability to transmit during distinct phases of infection is important to enable accurate predictions of the spread and impact of a disease outbreak. In the current investigation, the potential for transmission of foot-and-mouth disease virus (FMDV) during the incubation (preclinical) period of infection was investigated in seven groups of pigs that were sequentially exposed to a group of donor pigs that were infected by simulated-natural inoculation. Contact-exposed pigs were comingled with infected donors through successive 8-h time slots spanning from 8 to 64 h post-inoculation (hpi) of the donor pigs. The transition from latent to infectious periods in the donor pigs was clearly defined by successful transmission of foot-and-mouth disease (FMD) to all contact pigs that were exposed to the donors from 24 hpi and later. This onset of infectiousness occurred concurrent with detection of viremia, but approximately 24 h prior to the first appearance of clinical signs of FMD in the donors. Thus, the latent period of infection ended approximately 24 h before the end of the incubation period. There were significant differences between contact-exposed groups in the time elapsed from virus exposure to the first detection of FMDV shedding, viremia, and clinical lesions. Specifically, the onset and progression of clinical FMD were more rapid in pigs that had been exposed to the donor pigs during more advanced phases of disease, suggesting that these animals had received a higher effective challenge dose. These results demonstrate transmission and dissemination of FMD within groups of pigs during the incubation period of infection. Furthermore, these findings suggest that under current conditions, shedding of FMDV in oropharyngeal fluids is a more precise proxy for FMDV infectiousness than clinical signs of infection. These findings may impact modeling of the propagation of FMD outbreaks that initiate in pig holdings and should be considered when designing FMD control strategies.